ANALISIS KEGAGALAN DRUM REM PRODUKSI UKM UNTUK TRUK/BUS DENGAN DAYA MESIN 190 HP - Puja, IGN Wiratmaja; Suratman, Rochim; Suprihanto, Agus; Reza, Reza; Ako, Henry (Mesin, 2002)
Indonesian small and medium industries (UKM) have the ability to produce relatively cheap truck/bus brake drums, but the quality is needed to be improved. The drums usually fail in form of cracks or fractures before the design life is reached. This paper presents failure identification of the UKMâs brake drums that is including material aspects, operational loading, and stress analysis. The mechanical and physical properties of the materials are studied by conducting tensile test, hardness test, chemical composition, and metallography. Fractography is also conducted to study the type and process of the failures. The brake loads are analyzed for various operational conditions such as straight, curved, and downhill path, with various value of decceleration. Stress analysis of the drum due to the applied loads is conducted using finite element method. The complete analysis shows that the UKMâs drums are not strong enough for the applied braking load. It is also observed that the crack locations are in agreement with the highly computed stressed areas.